Comparing the effects of aqua- and land-based active cooldown exercises on muscle soreness and sport performance: a randomized crossover study - Chin, E. C.-Y.; Lai, S. C.-N.; Tsang, S.-F.; Chung, S. H.-N.; Wong, Y.-L.; Sran, N.; Fung, K.-K.; Sun, F. (International Journal of Sports Physiology and Performance, 2024)
Objective: Limited research has directly compared the effectiveness of aqua- and land-based exercises for postexercise recovery. This study aimed to fill this gap by comparing the effects of these 2 types of exercises on postexercise recovery.